ENGINEERING METHOD FOR CALCULATING STEEL-REINFORCED CONCRETE ELEMENTS WITH FLEXIBILITY - Yefimenko, Olena (Academic journal Industrial Machine Building Civil Engineering, 2019)
In the article presents an engineering method for calculating compressed flexible reinforced concrete elements with sheet reinforcement over a steel cross section. The results of the calculation are compared with the experimental data. Calculation ofload-bearing capacity of reinforced concrete flexible elements with sheet reinforcement is based on the method of boundarystates. The work of specimens under load and the nature of the load-bearing capacity depending on the height and eccentricity of the effort were investigated. The proposed method of calculating compressed elements with sheet reinforcement on asteel-cross-section allows to take into account their flexibility in both axial and out-of-center application of load.
Keywords: steel reinforced concrete; bearing capacity; sheet reinforcement; eccentricity; flexibility